Impaired glucose transporter-1 degradation and increased glucose transport and oxidative stress in response to high glucose in chondrocytes from osteoarthritic versus normal human cartilage - Rosa, SC (2011)
INTRODUCTION: Disorders that affect glucose metabolism, namely diabetes mellitus (DM), may favor the development and/or progression of osteoarthritis (OA). Thus far, little is known regarding the ability of chondrocytes to adjust to variations in the extracellular glucose concentration, resulting from hypoglycemia and hyperglycemia episodes, and so, to avoid deleterious effects resulting from deprivation or intracellular accumulation of glucose. The aim of this study was to compare the ability of normal and OA chondrocytes to regulate their glucose transport capacity in conditions of insufficient or excessive extracellular glucose and to identify the mechanisms involved and eventual deleterious consequences, namely the production of reactive oxygen species (ROS). METHODS: Chondrocytes, isolated from normal and OA human cartilage, were maintained in high-density monolayer cultures, in media without or with 10 or 30 mM glucose. Glucose transport was measured as the uptake of 2-deoxy-D-glucose (2-DG). Glucose transporter-1 (GLUT-1) mRNA and protein content were evaluated by real-time RT-PCR and western blot, respectively. ROS production was measured with 2',7'-dichlorodihydrofluorescein diacetate. RESULTS: Basal and IL-1beta-induced 2-DG uptake, including the affinity (1.066 +/- 0.284 and 1.49 +/- 0.59 mM) and maximal velocity (0.27 +/- 0.08 and 0.33 +/- 0.08 nmol/microg protein/hour), and GLUT-1 content were identical in normal and OA chondrocytes. Glucose deprivation increased 2-DG uptake and GLUT-1 protein both in normal and OA chondrocytes. Exposure to high glucose (30 mM) for 18 or 48 hours decreased those parameters in normal but not in OA chondrocytes. GLUT-1 mRNA levels were unaffected by high glucose, either in normal or OA chondrocytes. The high glucose-induced reduction in GLUT-1 protein in normal chondrocytes was reversed by treatment with a lysosome inhibitor. High glucose induced ROS production, which lasted significantly longer in OA than in normal chondrocytes. CONCLUSIONS: Normal human chondrocytes adjust to variations in the extracellular glucose concentration by modulating GLUT-1 synthesis and degradation which involves the lysosome pathway. Although capable of adjusting to glucose deprivation, OA chondrocytes exposed to high glucose were unable downregulate GLUT-1, accumulating more glucose and producing more ROS. Impaired GLUT-1 downregulation may constitute an important pathogenic mechanism by which conditions characterized by hyperglycemia, like DM, can promote degenerative changes in chondrocytes that can facilitate the progression of OA